The effect of the onset of seizure on clock drawing test score of epilepsy patients - Baiq Kania Kartika Yaksa; Herpan Syafii Harahap; Emmy Amalia; Yanna Indrayana (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
Background: Epilepsy is one of the causing factors of cognitive impairment which affects the patient’s quality of life. The most critical risk factor for cognitive impairment in epilepsy patients is the onset of seizure. Performing detection of cognitive impairment in those patients is crucial. Clock Drawing Test (CDT) is a validated instrument for the detection of cognitive impairment in epilepsy patients.Objective: This study was aimed to investigate the effect of the onset of seizure on CDT score in epilepsy patients.Methods: This study was a cross-sectional study involving 64 epilepsy patients of Mutiara Sukma Mental Hospital, West Nusa Tenggara, who met the inclusion but not exclusion criteria. The clinical and demographic characteristics data collected in this study were age, gender, type of seizure, etiology, length of education, duration of treatment, and antiepileptic drugs (AED). Cognitive function evaluation has been done by using the CDT instrument. Analysis of the effect of the beginning of seizure on CDT score was carried out by observing the influence of the clinical and demographic characteristics data.Results: There was a significant difference between the onset of seizure on CDT score (p<0.05). There were significant differences in aetiology and age in both groups of onsets of the seizure (p <0.05), but not in the characteristics of gender, type of seizure, level of education, duration of treatment and AED in both groups of onsets of the seizure (p>0.05).Conclusion: The onset of the seizure in epilepsy patients affect CDT score. This effect might be attributed to etiology and age of epilepsy patients.